A zinc metal negative electrode material modified with a dual-functional protective layer and its preparation method and application

By modifying the dual-function protective layer on the zinc metal negative electrode material, using the PVDF skeleton and acrylic monomer branched polymer powder, the instability problem of zinc metal negative electrode material in the aqueous electrolyte is solved, and a higher Kulun is achieved Efficiency and cycle stability while simplifying the production process and reducing costs.

CN115312714BActive Publication Date: 2025-02-11WUHAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210881287.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-26
Publication Date
2025-02-11
Estimated Expiration
2042-07-26

AI Technical Summary

Technical Problem

The thermodynamic and electrochemical instability of zinc metal anode materials in aqueous electrolytes leads to water-oxygen corrosion, by-product generation and zinc dendrites growth, reducing the coulomb efficiency and cycle life of the battery.

Method used

Using the method of dual-function protective layer modification, polyvinylidene fluoride (PVDF) is eliminated in potassium hydroxide/ethanol solution to obtain alkaline PVDF, and then radical polymerization is carried out with initiator and acrylic monomer to form a free-radical polymerization with the initiator and the acrylic monomer to form a protective The polymer powder with corrosion and uniform deposition functions is coated on the zinc metal surface and a protective layer is formed after vacuum drying.

Benefits of technology

It effectively suppresses side reactions such as hydrogen evolution and corrosion, provides a continuous zinc ion transport channel, promotes uniform deposition of zinc ions, improves the reversibility and cycle life of zinc metal negative electrodes, and reduces production costs and complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115312714B_ABST
    Figure CN115312714B_ABST
Patent Text Reader

Abstract

The present invention discloses a zinc metal negative electrode material modified with a dual-functional protective layer and a preparation method and application thereof. The preparation method comprises the following steps: polyvinylidene fluoride undergoes an elimination reaction in a potassium hydroxide / ethanol solution to obtain alkalized polyvinylidene fluoride; alkalized polyvinylidene fluoride, an initiator and an acrylic acid monomer are dissolved in a solvent to undergo free radical polymerization, and the product is washed and dried to obtain a polymer powder; the polymer powder is dissolved in the solvent to obtain a dispersion, and the dispersion is coated on the surface of zinc metal, and the zinc metal negative electrode material modified with a dual-functional protective layer is obtained after vacuum drying. The present invention constructs a dual-functional protective layer on the surface of a zinc metal negative electrode by a coating method, which can both inhibit corrosion and promote uniform deposition and is tightly bonded to a zinc substrate, and is beneficial to the stable circulation of the zinc negative electrode during the charge and discharge process, thereby improving the electrochemical performance and cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a zinc metal negative electrode material modified with a dual-functional protective layer, and a preparation method and application thereof. Background Art

[0002] With the continuous increase in the market of rechargeable secondary batteries, people have put forward higher requirements for battery safety and environmental protection. The further development of lithium-ion batteries, which currently occupy a leading position, has been hindered by their low element reserves, high cost and poor safety. Rechargeable aqueous zinc-ion batteries with high element reserves, low cost and high safety have become favorable candidates to replace lithium-ion batteries. However, the thermodynamic and electrochemical instability of metallic zinc, which is the most preferred negative electrode material for zinc-ion batteries, in aqueous electrolytes is an urgent problem to be solved. During the charge and discharge process, the surface of zinc metal will suffer severe water-oxygen corrosion, producing a large amount of by-products such as zinc hydroxysulfate. At the same time, zinc ions tend to nucleate at positions with lower energy, forming a tip effect and gradually growing into zinc dendrites, reducing the coulomb efficiency of the battery. The zinc dendrites that continue to grow may even pierce the diaphragm, causing battery failure.

[0003] So far, a lot of work has been used to solve the above problems, such as constructing three-dimensional electrode structures to regulate zinc ion flux, preparing high-concentration electrolytes, and using electrolyte additives to change the solvation structure. However, these methods are limited by complex preparation processes and high costs. Modifying the functional layer on the surface of metallic zinc is a simple and effective method. Among them, inorganic nanoparticle coatings such as calcium carbonate and kaolin have been widely studied, but their weak adsorption and brittleness with metallic zinc make them easy to fall off when the volume expands due to electrochemical reactions. Considering the adhesion and mechanical adaptability of polymers, combining inorganic and organic is a feasible strategy, such as combining PVDF with TiO2. However, nanoparticles are easy to agglomerate in polymer solvents and are not easy to be evenly dispersed in organic solvents, which will lead to the failure of precise transmission of zinc ions. At the same time, the high cost of nanoparticle preparation still limits the large-scale production and application of low-cost aqueous zinc-ion batteries. Pure polymer coatings have good mechanical properties and can adapt to volume expansion during charge and discharge, but most polymer coatings increase the nucleation overpotential of zinc ions, which is not conducive to uniform deposition. We can modify existing polymers through chemical means such as grafting to make it both suppress side reactions and promote uniform deposition. This method is low-cost and simple in process, and has broad prospects in the protection of zinc metal anodes. Summary of the invention

[0004] In view of this, the present invention provides a zinc metal negative electrode material modified with a dual-functional protective layer and a preparation method and application thereof, so as to solve the problem of thermodynamic and electrochemical instability of the negative electrode of the existing aqueous zinc ion battery during the cycle process.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer comprises the following steps:

[0007] S1, polyvinylidene fluoride undergoes elimination reaction in potassium hydroxide / ethanol solution to obtain alkalized polyvinylidene fluoride;

[0008] S2, dissolving alkalized polyvinylidene fluoride, an initiator and acrylic acid monomer in a solvent to perform free radical polymerization, and washing and drying the product to obtain a polymer powder;

[0009] S3, dissolving the polymer powder in the solvent to obtain a dispersion, coating the dispersion on the surface of zinc metal, and obtaining a zinc metal negative electrode material modified with a dual-functional protective layer after vacuum drying.

[0010] According to the above scheme, in step S1, the concentration of the potassium hydroxide / ethanol solution is 0.5-4M.

[0011] According to the above scheme, in step S2, the mass ratio of the alkalized polyvinylidene fluoride, the initiator and the acrylic acid monomer is 12:(1-3):(3-9).

[0012] According to the above scheme, the initiator includes one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate initiators.

[0013] According to the above scheme, in steps S2 and S3, the solvent includes one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and triethyl phosphate.

[0014] According to the above scheme, in step S3, the vacuum drying temperature is 45-60°C.

[0015] According to the above scheme, in step S3, the coating method includes one of spin coating, scraper coating, spray coating, dip coating and 3D printing.

[0016] On the basis of the above scheme, the second purpose of the present invention is to provide a zinc metal negative electrode material modified with a dual-functional protective layer, which is prepared by the preparation method of the zinc metal negative electrode material modified with a dual-functional protective layer described above.

[0017] The dual-functional protective layer-modified zinc metal negative electrode material comprises a metal layer and a protective layer covering the metal layer, and the thickness of the protective layer is in the range of 5 μm to 30 μm.

[0018] On the basis of the above scheme, the third purpose of the present invention is to provide the application of the zinc metal negative electrode material modified with the above-mentioned dual-functional protective layer in aqueous zinc ion batteries.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] (1) The zinc metal negative electrode material modified with a dual-functional protective layer provided by the present invention, on the one hand, blocks the active water molecules and oxygen in the electrolyte from directly contacting the zinc metal surface through the PVDF skeleton in the protective layer, thereby inhibiting side reactions such as hydrogen evolution and corrosion; on the other hand, the carboxyl groups in the polyacrylic acid side chains have a strong adsorption effect on water, and the carboxyl groups of multiple zinc-philic functional groups work together to provide a continuous transmission channel for zinc ions, inducing uniform deposition of zinc ions, thereby improving the reversibility and cycle life of the zinc metal negative electrode.

[0021] (2) The preparation method provided by the present invention is relatively simple to operate, has a short synthesis time, mild reaction conditions, low cost, is green and environmentally friendly, has good repeatability, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 The scanning electron microscope (SEM) images of the planes of the PgP-Zn pole piece (b) and the bare zinc (a) described in Example 1 of the present invention;

[0024] Figure 2 This is a SEM image of a cross section of the PgP-Zn pole piece described in Example 1 of the present invention;

[0025] Figure 3 The zinc-zinc symmetric battery assembled by the PgP-Zn pole piece and bare zinc in Example 1 of the present invention is 1 mA cm -2 Current density and 1mAh cm -2 Long cycle performance diagram at surface capacity;

[0026] Figure 4 The zinc-zinc symmetric battery assembled by the PgP-Zn pole piece (b) and bare zinc (a) described in Example 1 of the present invention is 1 mA cm -2Current density and 1mAh cm -2 Planar SEM image after 200h of cycling at surface capacity;

[0027] Figure 5 The zinc-zinc symmetric battery assembled by the PgP-Zn pole piece and bare zinc in Example 1 of the present invention is 1 mA cm -2 Current density and 1mAh cm -2 Comparison of XRD results after 200h of cycling at surface capacity;

[0028] Figure 6 The zinc-zinc symmetric battery assembled by the PgP-Zn pole piece and bare zinc in Example 1 of the present invention is 8 mA cm -2 The high current density and 1 mAh cm -2 Long cycle performance diagram at surface capacity;

[0029] Figure 7 The Zn||Bare Cu and Zn||PgP-Cu half-cells, which are assembled with bare copper and Cu foil coated with a PgP dual-functional protective layer and bare zinc, respectively, are charged at 2 mA cm -2 Current density and 1mAh cm -2 Comparison of Coulombic efficiency obtained by cycling under surface capacity;

[0030] Figure 8 This is a long cycle performance diagram of a full battery assembled with the PgP-Zn electrode and bare zinc and synthetic MnO2 described in Example 1 of the present invention at a current density of 3C. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0032] It should be noted that in the description of the embodiments of the present application, the description of the term "some specific embodiments" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0033] In this embodiment, “in the range of…” includes both end values, such as “in the range of 1 to 100” includes both end values ​​of 1 and 100.

[0034] The embodiment of the present invention provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, comprising the following steps:

[0035] S1. Elimination reaction of polyvinylidene fluoride PVDF occurs in a potassium hydroxide / ethanol solution to obtain alkalized polyvinylidene fluoride HPVDF, which is then washed and dried for later use; wherein the concentration of the potassium hydroxide / ethanol solution is 0.5-4M.

[0036] S2, dissolving alkalized polyvinylidene fluoride HPVDF, an initiator and acrylic acid monomer in a solvent to perform free radical polymerization, and washing and drying the product to obtain a polymer powder;

[0037] The mass ratio of alkalized polyvinylidene fluoride, initiator and acrylic monomer is 12:(1-3):(3-9); the initiator includes one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate initiator; and the solvent includes one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) and triethyl phosphate (TEP).

[0038] Therefore, the zinc-philic functional groups can be grafted onto the polymer with anti-corrosion function by using the free radical polymerization method.

[0039] S3. Dissolve the polymer powder in a solvent to obtain a dispersion, apply the dispersion on the surface of zinc metal, and vacuum dry at 45-60° C. to obtain a dual-functional protective layer modified zinc metal negative electrode material.

[0040] The coating method includes one of spin coating, scraping, spraying, dipping and 3D printing. In the present invention, the spin coating method is preferably used.

[0041] Thus, the polymer powder is evenly dispersed in the solvent, evenly coated on the surface of the zinc sheet by spin coating, and finally vacuum dried to dry the solvent to construct a dendrite-free, highly reversible zinc metal anode. The anti-corrosion polymer skeleton in the protective layer can prevent water and oxygen in the electrolyte from directly contacting the surface of the zinc sheet, thereby avoiding side reactions; at the same time, the zinc-philic functional group carboxyl (-COOH) provides a continuous transmission channel for zinc ions through strong adsorption with zinc ions, thereby regulating the deposition behavior of zinc.

[0042] Another embodiment of the present invention provides a zinc metal negative electrode material modified with a dual-functional protective layer, which is prepared by the above-mentioned method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer.

[0043] The dual-functional protective layer comprises a metal layer of zinc metal negative electrode material and a protective layer covering the metal layer. The protective layer is based on polymer PVDF, has an average relative molecular weight of more than 100,000, and has a thickness in the range of 5 μm to 30 μm.

[0044] Based on the above scheme, another embodiment of the present invention provides the application of the zinc metal negative electrode material modified with the above dual-functional protective layer in an aqueous zinc ion battery.

[0045] Of course, it is understandable that although the present invention takes zinc metal as an example to prepare the negative electrode material, the preparation method described in the present invention is also applicable to lithium, sodium, and potassium metal negative electrodes, which will not be described one by one here.

[0046] On the basis of the above-mentioned embodiments, the present invention provides the following specific examples to further illustrate the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The experimental methods without specifying specific conditions in the following examples are usually based on the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by mass.

[0047] Example 1

[0048] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, comprising the following steps:

[0049] 1) Add 0.5 g of PVDF to 20 ml of 2 M KOH / ethanol solution, stir in a 60°C water bath for 2 h, centrifuge the mixed solution, wash with ethanol and deionized water three times each, and bake at 70°C for 24 h to obtain HPVDF with double bonds;

[0050] 2) 0.4 g HPVDF was added to 30 ml NMP and stirred in a water bath at 50° C. for 1 h. 0.033 g azobisisobutyronitrile and 2.06 ml acrylic acid were then added to the solution and the temperature was raised to 80° C. and stirred for 2 h. Finally, the resulting solution was centrifuged and washed with ethanol and deionized water for 3 times each. The resulting sample was placed in a vacuum oven at 70° C. for 24 h to obtain a polymer powder grafted with PAA on PVDF (denoted as PgP).

[0051] 3) 0.5 g of PgP powder was dissolved in 15 ml of NMP and stirred at room temperature for 7 days to obtain a dispersion. 1 mL of the dispersion was spin-coated on a zinc sheet (the zinc sheet was a disc with a thickness of 100 μm and a diameter of 5 cm) at a spin coating speed of 1000 r / s for 10 s. The zinc sheet was placed on a hot plate at 70°C and baked for 2 min. This step was repeated twice (the last time without placing it on the hot plate). Finally, the coated zinc sheet was placed in a vacuum drying oven at 60°C for 24 h to dry the solvent, thereby obtaining a zinc metal negative electrode material modified with a dual-functional protective layer (denoted as PgP-Zn).

[0052] Taking the PgP-Zn electrode and bare zinc (denoted as Bare Zn) prepared in Example 1 as an example, the morphology and structure were characterized and the results were obtained. Figure 1-2 The result graph is shown.

[0053] Figure 1 (a) is the SEM image of the bare Zn plane. Figure 1 (b) is a planar SEM image of the PgP-Zn electrode. It can be seen from the image that after coating with the protective layer, the surface of the zinc sheet becomes smoother and flatter.

[0054] Figure 2 The SEM image of the cross section of the PgP-Zn electrode. Figure 2 It can be seen that the thickness of the coated dual-function protective layer is about 14.6 μm.

[0055] The zinc-zinc symmetric battery (the electrolyte used was 2M ZnSO4 solution) assembled with the zinc metal negative electrode material modified with the dual-functional protective layer prepared in Example 1 and bare zinc was subjected to electrochemical testing to obtain Figure 3-6 The result graph is shown.

[0056] Figure 3 The symmetric Zn-Zn battery assembled with PgP-Zn electrode and Bare Zn at 1 mA cm -2 Current density and 1mAhcm -2 Long cycle performance diagram under surface capacity, from Figure 3 It can be seen that the symmetrical battery assembled with Bare Zn has a polarization of more than 150 mV at 200 h and a short circuit at 240 h, while the symmetrical battery assembled with PgP-Zn pole pieces can be stably cycled for 2500 h and maintain a polarization of less than 25 mV.

[0057] Figure 4 (a) and (b) are symmetrical Zn-Zn cells assembled with bare Zn and PgP-Zn electrodes (the electrolyte used is 2 M ZnSO4 solution) at 1 mA cm -2 Current density and 1mAh cm -2 Comparison of X-ray diffraction (XRD) results after 200h of cycling at surface capacity. Figure 4 It can be seen that there are a large number of flaky dendrites and glass fiber separators on the bare zinc surface, while the PgP-Zn surface is clean and flat without obvious dendrite formation.

[0058] Figure 5 The symmetric Zn-Zn battery assembled with PgP-Zn electrode and Bare Zn at 1 mA cm -2 Current density and 1mAhcm -2 XRD diagram after 200h of cycling at surface capacity. Figure 5 It can be seen that a large amount of Zn4(OH)6·xH2O by-products appeared on the surface of bare zinc after cycling, while only a small amount of by-products appeared on the surface of the PgP-Zn electrode.

[0059] Figure 6 The symmetric Zn-Zn battery assembled with PgP-Zn electrode and Bare Zn at 8 mA cm -2 The high current density and 1 mAh cm -2 Long cycle performance diagram under surface capacity, from Figure 6 It can be seen that the symmetrical battery assembled with Bare Zn quickly short-circuited, while the symmetrical battery assembled with PgP-Zn pole pieces could be stably cycled for 550 h and maintain a polarization of less than 60 mV.

[0060] Figure 7 For Zn||Bare Cu and Zn||PgP-Cu half-cells (the electrolyte used is 2M ZnSO4 solution) at 2mAcm -2 Current density and 1mAh cm -2 Comparison of Coulombic efficiency obtained by cycling under surface capacity. The mechanism of this test is that 1mAh cm -2 The zinc ions are first dissolved from the zinc metal negative electrode and deposited on the working electrode Cu during discharge. Then, during charging, it is checked how many zinc ions can be stripped off from Cu. The ratio of the stripping and deposition amounts is the coulombic efficiency.

[0061] from Figure 7 It can be seen that the coulombic efficiency of the Zn||Bare Cu half-cell fluctuates greatly at 180 cycles, even exceeding 150%, indicating that the battery has been short-circuited; while the Zn||PgP-Cu half-cell can stably cycle 2700 cycles and obtain an ultra-high coulombic efficiency of 99.88%, indicating that the PgP dual-functional protective layer can significantly improve the coulombic efficiency of the zinc negative electrode during the cycle process.

[0062] Figure 8 The full cell assembled with PgP-Zn electrode and bare Zn and synthesized MnO2 (the electrolyte used was 2M ZnSO4+0.2M MnSO4 solution) at 3C (1C=308mA g -1 ) Long cycle performance diagram under current density, from Figure 8 It can be seen that the coulombic efficiency of both is close to 100%; in terms of capacity retention, after 900 cycles, the full battery assembled with Bare Zn has only a capacity retention rate of 49%, while the full battery assembled with PgP-Zn has a capacity retention rate of 80%.

[0063] The PgP-Zn electrode was assembled with the synthesized MnO2 into a soft-pack battery (the electrolyte used was 2MZnSO4+0.2MMnSO4 solution). After testing, the soft-pack battery showed a normal open circuit voltage of 1.417V, and the voltage did not change much after bending and shearing. The soft-pack battery can successfully light up the LED signboard.

[0064] From the above tests, it can be seen that the zinc metal negative electrode material modified with a dual-functional protective layer provided in the present application is grafted with PAA with a zinc-philic functional group on the PVDF chain with an anti-corrosion function, and then the grafted polymer is coated on the surface of the zinc metal to obtain a PgP-Zn electrode as an aqueous zinc ion battery negative electrode. In the method of the present invention, the PVDF skeleton can block the active water molecules and oxygen in the electrolyte from directly contacting the zinc metal surface, thereby inhibiting side reactions such as hydrogen evolution and corrosion; at the same time, the -COOH in the PAA side chain has a strong adsorption effect on water, and multiple -COOHs work together to provide a continuous transmission channel for zinc ions, inducing uniform deposition of zinc ions. With these two functions of the PgP dual-functional layer, the PgP-Zn negative electrode has a higher coulomb efficiency and better cycle stability, thereby greatly improving the battery life.

[0065] Example 2

[0066] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from that of Embodiment 1 in that: in step 1), 0.5 g of PVDF is added to 20 ml of a 0.5 M KOH / ethanol solution;

[0067] The remaining steps and parameters are the same as those in Example 1.

[0068] Example 3

[0069] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0070] In step 1), 0.5 g of PVDF was added to 20 ml of 1 M KOH / ethanol solution;

[0071] The remaining steps and parameters are the same as those in Example 1.

[0072] Example 4

[0073] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0074] In step 1), 0.5 g of PVDF was added to 20 ml of 3 M KOH / ethanol solution;

[0075] The remaining steps and parameters are the same as those in Example 1.

[0076] Example 5

[0077] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0078] In step 1), 0.5 g of PVDF was added to 20 ml of 4 M KOH / ethanol solution;

[0079] The remaining steps and parameters are the same as those in Example 1.

[0080] Example 6

[0081] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0082] In step 2), 0.033 g of azobisisobutyronitrile and 1.03 ml of acrylic acid were added;

[0083] The remaining steps and parameters are the same as those in Example 1.

[0084] Example 7

[0085] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0086] In step 2), 0.033 g of azobisisobutyronitrile and 3.09 ml of acrylic acid were added;

[0087] The remaining steps and parameters are the same as those in Example 1.

[0088] Example 8

[0089] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0090] In step 2), 0.033 g of azobisisobutyronitrile and 4.12 ml of acrylic acid were added;

[0091] The remaining steps and parameters are the same as those in Example 1.

[0092] Example 9

[0093] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0094] In step 3), the spin coating speed is 2000 r / s, and the remaining steps and parameters are the same as those in Example 1.

[0095] Example 10

[0096] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0097] In step 3), the spin coating speed is 3000 r / s, and the remaining steps and parameters are the same as those in Example 1.

[0098] Embodiment 11

[0099] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0100] In step 3), the spin coating and drying steps are not repeated, and the remaining steps and parameters are the same as those in Example 1.

[0101] Example 12

[0102] This embodiment provides a method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0103] In step 3), the spin coating and drying steps are repeated once, and the remaining steps and parameters are the same as those in Example 1.

[0104] Embodiment 13

[0105] This embodiment provides a method for preparing a lithium metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0106] In step 3), 1 mL of the dispersion was spin-coated on the lithium sheet, and the remaining steps and parameters were the same as those in Example 1.

[0107] Embodiment 14

[0108] This embodiment provides a method for preparing a sodium metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0109] In step 3), 1 mL of the dispersion was spin-coated on the sodium sheet, and the remaining steps and parameters were the same as those in Example 1.

[0110] Embodiment 15

[0111] This embodiment provides a method for preparing a potassium metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0112] In step 3), 1 mL of the dispersion was spin-coated on the potassium sheet, and the remaining steps and parameters were the same as those in Example 1.

[0113] Example 16

[0114] This embodiment provides a method for preparing a magnesium metal negative electrode material modified with a dual-functional protective layer, which is different from Embodiment 1 in that:

[0115] In step 3), 1 mL of the dispersion was spin-coated on a magnesium sheet, and the remaining steps and parameters were the same as those in Example 1.

[0116] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a zinc metal negative electrode material modified with a dual-functional protective layer, characterized in that: The steps include: S1, polyvinylidene fluoride undergoes elimination reaction in potassium hydroxide / ethanol solution to obtain alkalized polyvinylidene fluoride; S2, dissolving alkalized polyvinylidene fluoride, an initiator and acrylic acid monomer in a solvent to perform free radical polymerization, and washing and drying the product to obtain a polymer powder; S3, dissolving the polymer powder in the solvent to obtain a dispersion, coating the dispersion on the surface of zinc metal, and obtaining a zinc metal negative electrode material modified with a dual-functional protective layer after vacuum drying.

2. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the potassium hydroxide / ethanol solution is 0.5-4M.

3. The preparation method according to claim 1 or 2, characterized in that: In step S2, the mass ratio of the alkalized polyvinylidene fluoride, the initiator and the acrylic acid monomer is 12:(1-3):(3-9).

4. The preparation method according to claim 3, characterized in that: The initiator includes one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate initiator.

5. The preparation method according to claim 1, characterized in that: In steps S2 and S3, the solvent includes one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and triethyl phosphate.

6. The preparation method according to claim 5, characterized in that: In step S3, the vacuum drying temperature is 45-60°C.

7. The preparation method according to claim 5, characterized in that: In step S3, the coating method includes one of spin coating, scraper coating, spray coating, dip coating and 3D printing.

8. A zinc metal negative electrode material modified with a dual-functional protective layer, characterized in that: The zinc metal negative electrode material is prepared by the preparation method of the dual-functional protective layer modified by any one of claims 1 to 7.

9. The zinc metal negative electrode material modified with a dual-functional protective layer according to claim 8, characterized in that: The invention comprises a metal layer and a protection layer covering the metal layer, wherein the thickness of the protection layer is in the range of 5 μm to 30 μm.

10. Use of the zinc metal negative electrode material modified with a dual-functional protective layer obtained by the preparation method according to any one of claims 1 to 7 or the zinc metal negative electrode material modified with a dual-functional protective layer according to claim 8 or 9 in an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Zinc negative electrode material with elastic protective layer, preparation and application thereof

    CN111600025A

  • Aqueous zinc ion battery electrolyte and preparation method and application thereof

    CN113078371A

  • Protective layer modified zinc negative electrode material and preparation method and application thereof

    CN114725336A

  • Polyvinylidene difluoride structure

    US4774132A